First brown lacewings (Neuroptera: Hemerobiidae) from the early Eocene Green River Formation - Makarkin, Vladimir N. (Zootaxa, 2024)
Pseudonotherobius kohlsi gen. et sp. nov. and Megalomus? coloradensis sp. nov. (Neuroptera: Hemerobiidae) are described from the early Eocene of the Parachute Creek Member of the Green River Formation, Colorado, U.S.A. The main diagnostic character states of Pseudonotherobius gen. nov. are the presence of a crossvein between the proximal branch of RP and RA in the forewing, and the costal space being dilated medially in the hind wing. The latter condition is unique in the family. The genus is preliminarily assigned to the subfamily Carobiinae due to the similarity of its venation to that of the extant Australian genus Notherobius New, 1988.